2015
DOI: 10.1016/j.neulet.2014.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Dual-hemisphere transcranial direct current stimulation over primary motor cortex enhances consolidation of a ballistic thumb movement

Abstract: Transcranial direct current stimulation (tDCS) is a noninvasive technique that modulates motor performance and learning. Previous studies have shown that tDCS over the primary motor cortex (M1) can facilitate consolidation of various motor skills. However, the effect of tDCS on consolidation of newly learned ballistic movements remains unknown. The present study tested the hypothesis that tDCS over M1 enhances consolidation of ballistic thumb movements in healthy adults. Twenty-eight healthy subjects participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 35 publications
0
14
2
1
Order By: Relevance
“…For example, there have been rapid consolidation effects where group differences only begin to emerge in the minutes or hours after stimulation, or become stronger/more robust with time (e.g., Clark et al 2012;Ehsani et al 2016;Hoy et al 2014;Javadi and Cheng 2013;Penolazzi et al 2013;Reis et al 2015). Similarly, overnight consolidation has been enhanced when performance is measured the next day, despite a lack of group differences on day 1 (Koyama et al 2015;Martin et al 2014), and even cognitive training studies that failed to show immediate tDCS-related enhancements have still demonstrated greater tDCS-related retention a couple months later (Jones et al 2015;Martin et al 2013;Stephens and Berryhill 2016).…”
Section: Experimental Evidencementioning
confidence: 99%
“…For example, there have been rapid consolidation effects where group differences only begin to emerge in the minutes or hours after stimulation, or become stronger/more robust with time (e.g., Clark et al 2012;Ehsani et al 2016;Hoy et al 2014;Javadi and Cheng 2013;Penolazzi et al 2013;Reis et al 2015). Similarly, overnight consolidation has been enhanced when performance is measured the next day, despite a lack of group differences on day 1 (Koyama et al 2015;Martin et al 2014), and even cognitive training studies that failed to show immediate tDCS-related enhancements have still demonstrated greater tDCS-related retention a couple months later (Jones et al 2015;Martin et al 2013;Stephens and Berryhill 2016).…”
Section: Experimental Evidencementioning
confidence: 99%
“…Galea and Celnik (2009) showed a significant effect on training by applying tDCS during the training, an effect that is similarly found with sequence-learning (Stagg et al, 2011). Furthermore, recent results showed enhanced retention of ballistic thumb movements when M1-atDCS was applied during training when evaluating both peak velocities and accelerations of thumb movements (Koyama et al, 2015; Rroji et al, 2015). …”
Section: Modulating Motor Learning Processes Through Tdcsmentioning
confidence: 99%
“…We applied a bihemispheric tDCS protocol, which is a powerful strategy for controlling brain excitability and various neurological functions. Because of its greater impact on interhemispheric projections, bihemispheric tDCS applied simultaneously is more effective than unihemispheric tDCS for modulating motor performance and sensory perception 15 , 16 . Thus, bihemispheric tDCS potentiates the effects of anodal stimulation to one hemisphere through additional modulation of interhemispheric interactions by cathodal stimulation to the contralateral hemisphere.…”
Section: Introductionmentioning
confidence: 99%